A Case Series: Describing the Coronavirus Pandemic Response in Small Naval OCONUS Military Treatment Facilities. Issue 9 (1st September 2021) - Latimer, Emily R; Parker, Christopher A; Swiger, Pauline A
ABSTRACT: Introduction: The European SARS-CoV-2 (COVID-19) outbreak threatened military beneficiaries receiving care outside of the United States. Military treatment facilities located outside the United States were the first to respond to the pandemic, requiring immediate action to establish novel protocols. The purpose of this case series is to describe challenges, solutions, and future recommendations during a pandemic response at three small naval military treatment facilities located outside the continental United States (OCONUS). Results: The analysis and discussion reviews challenges in information processing, communication methods and patterns, process changes, actions for staff protection, and change fatigue experienced during this time. Conclusions: Recommendations for future work include filling the gaps in the evidence for a prolonged pandemic response and crisis management, such as the current SARS-CoV-2 pandemic, including best practices to communicate, maintain staff resilience, and manage or mitigate associated prolonged stress and uncertainty.